Philosophy of Leibniz - "Russell, Bertrand" (London, 2002)
Mr Russell's very brilliant criticism of Leibniz ... is a piece of controversial philosophy as well as a contribution to history.' - Bernard Bosanquet
Keywords: "Leibniz,Gottfried wilhem,1646-1716"